EXPLORING THE RELATIONSHIP BETWEEN BOARD AND SHARIAH GOVERNANCE QUALITY AND COSMETIC ACCOUNTING DURING COVID-19: A CONCEPTUAL STUDY OF MALAYSIAN FINANCIAL INSTITUTIONS - Uyob, Suzilawati; Yusof, Nurul Adillah; Awg Isa, Wan Rosnah; Md Zin, Ana Salwa; Hassan, Muhammad; Md Kassim, Aza Azlina; Diansari, Rani Eka (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The COVID-19 pandemic has intensified financial pressures on banking institutions, raising concerns about the integrity of financial reporting practices. This conceptual study explores the relationship between board governance and Shariah governance quality and the prevalence of cosmetic accounting practices among Malaysian financial institutions during the COVID-19 crisis. Anchored in Bank Governance Theory, the study examines how the structure, independence, and effectiveness of both conventional boards and Shariah supervisory boards influence the tendency to engage in cosmetic accounting as a response to external shocks. Malaysia’s dual banking system provides a unique context to assess how governance mechanisms within Islamic financial institutions interact with crisis-related incentives to present an enhanced but potentially misleading financial image. The study also considers how the pressures and disruptions caused by the pandemic may have altered the governance-accounting dynamic. By developing this conceptual model, the study aims to contribute to the broader discourse on governance and ethical financial reporting, offering insights for policymakers, regulators, and practitioners seeking to strengthen corporate governance standards in the post-pandemic financial landscape.